2015
DOI: 10.1128/jvi.01675-15
|View full text |Cite
|
Sign up to set email alerts
|

Novel Reassortant Human-Like H3N2 and H3N1 Influenza A Viruses Detected in Pigs Are Virulent and Antigenically Distinct from Swine Viruses Endemic to the United States

Abstract: Human-like swine H3 influenza A viruses (IAV) were detected by the USDA surveillance system. We characterized two novel swine human-like H3N2 and H3N1 viruses with hemagglutinin (HA) genes similar to those in human seasonal H3 strains and internal genes closely related to those of 2009 H1N1 pandemic viruses. The H3N2 neuraminidase (NA) was of the contemporary human N2 lineage, while the H3N1 NA was of the classical swine N1 lineage. Both viruses were antigenically distant from swine H3 viruses that circulate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
104
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 98 publications
(113 citation statements)
references
References 48 publications
(59 reference statements)
9
104
0
Order By: Relevance
“…Previous papers demonstrated that antigenic evolution was associated with reassortment [6,18,21,22] and here we observed an increase in HA diversity concurrent with reassortment between the endemic H1 lineages and the H1N1pdm09. Vaccines against IAV are routinely used in swine in the US; however, the continued presence of such a diverse population of swine H1 IAV may limit the effectiveness of these vaccines [19,[31][32][33].…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Previous papers demonstrated that antigenic evolution was associated with reassortment [6,18,21,22] and here we observed an increase in HA diversity concurrent with reassortment between the endemic H1 lineages and the H1N1pdm09. Vaccines against IAV are routinely used in swine in the US; however, the continued presence of such a diverse population of swine H1 IAV may limit the effectiveness of these vaccines [19,[31][32][33].…”
Section: Discussionsupporting
confidence: 61%
“…In this study, we identified the genome patterns of H1N1 and H1N2 collected from swine in the United States from 2009 to 2016. Similar studies with H3N2 viruses from US swine populations have been previously reported [6,23], but a comprehensive analysis of H1 IAV was lacking. Among the 616 unique genome sets for H1N1 and H1N2 viruses, 74 whole-genome patterns and 47 NA+internal patterns were identified.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…In this tree, the swine isolate from Guatemala still clustered in a separate clade from the vaccine lineages but with viruses from other geographic regions, indicating that the circulation of viruses from this clade was not exclusive to Central America. Inclusion of HA sequences of recent human‐like swine isolates 26 revealed that viruses from the same clade as the 040078‐H3N2 have been recently introduced in pigs in the United States.…”
Section: Resultsmentioning
confidence: 99%
“…The mutations in the HA1 protein of 040078‐H3N2 in comparison with the vaccine strains suggest differences in antigenicity with other viruses of human origin. Significant antigenic distance was shown for recent swine isolates from the same genetic cluster,26 meaning that even when other H3 viruses already circulate in pigs in Guatemala, there could be little cross‐protection to a virus like the 040078‐H3N2. Experimental evaluation of the transmissibility of this virus in pigs could help assess the risk of onward transmission in this host.…”
Section: Discussionmentioning
confidence: 99%